Geographical indications of fruit crops - R, Raghavendra H; Hiremath, Varun; K, Tejukumar B; V, Udaya T (Indian Horticulture, 2022)
Our country has mega-diversified climate and productive soil for cultivation providing ample of opportunities for the development of fruit industry. But the hardest challenge in present situation is to be produce self- sufficient in production to feed the ever increasing human population. The infusion of technology is needed for deriving higher output per unit area for competition both in domestic and international market. In India, many varieties of different fruit crops are growing under specific climate and in a specific zone of climate. This specific type of climate is responsible for conferring some unique characteristics to that particular variety of fruit crop. In this regard, the concept of geographical indications highlights the facts regarding quality and other parameters of the produce. Among 86 horticultural products, fruits cover 43% maximum share to the total number of GI’s. Twenty nine fruit goods have been registered covering crops like Mango, Banana, Citrus, Guava, Grapes, Pineapple, Pomegranate, Litchi, Strawberry, Jackfruit, Custard apple and Fig.